Diversity of Weeds in Rice Cultivation (Oryza sativa L.) in Tahoa Village, Kolaka District, Kolaka Regency - Maretik, Maretik; Fitra, Ramad Arya; Saif, Marfira; Yanti, Yanti; Mehora, Sutrisnawati; Handayani, Fitrianti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Rice weeds are one of the pest organisms that can reduce production yields.rice because own allelophaty which are parasitic and kill plants directly.The existence of weeds has received little attention from the community in Tahoa Village, even though their existence can damage rice plants (Oryza sativa L.). Purpose of this research can provides information related to the diversity of weed types and their evenness in ricecultivation in Tahoa Village, Kolaka. Sampling was carried out bymaking a plot size of 1 mx 1 m as many as 27 plots divided into 3 stations. The data obtained will be analyzed descriptively and quantitatively and then displayed in the form of tables anddocumentation. Based on the results of the study in Tahoa Village, Kolaka District, Kolaka Regency, 6 families, 8 genera and 8 species were found, namely Digitalia ciliaris, Cynodondactylon, Paspalum scropiculatum L, Alternanthera sessilis L, Sphenoclea zeylanica Geartn., Oldenlandia corymbosaL, Ludwigia octovalvis And Fimbristylis miliacea L. Based on the research results, the most species found were Sphenoclea zeylanica Geartn.. The diversity index (H') of the three stations, namely H'(1.62) states that the diversity of the research location is classified as moderate. The evenness index (E) of the three stations, namely E (0.78) states that the weed evenness index at the research location is classified as high. This is because these weeds have high adaptability to environmental changes both in drought and rain conditions. However, further study is needed regarding the physiology of the weeds found to obtain information regarding their parasitic nature on rice plants.